2014
DOI: 10.1371/journal.pone.0107320
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Cortical Complexity in Children with Prader-Willi Syndrome and Its Association with Cognitive Impairment and Developmental Delay

Abstract: BackgroundPrader-Willi Syndrome (PWS) is a complex neurogenetic disorder with symptoms involving not only hypothalamic, but also a global, central nervous system dysfunction. Previously, qualitative studies reported polymicrogyria in adults with PWS. However, there have been no quantitative neuroimaging studies of cortical morphology in PWS and no studies to date in children with PWS. Thus, our aim was to investigate and quantify cortical complexity in children with PWS compared to healthy controls. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…Specifically, the age × cognitive interaction effects provide evidence that the relationships between local cortical gyrification and sustained attention, inhibitory control, motor response variability, perceptual sensitivity, and both verbal and nonverbal conceptualization abilities differ at different ages during adolescence. These changing brain-behavior relationships were mostly but not exclusively seen in frontoparietal and temporoparietal brain regions where local gyrification values linearly decreased with age and where prior studies show links to individual differences in intellectual ability for healthy adults (Docherty et al, 2015; Gregory et al, 2016) and individuals with neurodevelopmental disorders (Lukoshe et al, 2014; Treble et al, 2013). Even though these interaction effects were found for all tests examined and in widespread frontoparietal cortices, statistical mediation analyses showed age-related changes in cortical folding causally influenced only motor response inhibition ability.…”
Section: Discussionmentioning
confidence: 86%
“…Specifically, the age × cognitive interaction effects provide evidence that the relationships between local cortical gyrification and sustained attention, inhibitory control, motor response variability, perceptual sensitivity, and both verbal and nonverbal conceptualization abilities differ at different ages during adolescence. These changing brain-behavior relationships were mostly but not exclusively seen in frontoparietal and temporoparietal brain regions where local gyrification values linearly decreased with age and where prior studies show links to individual differences in intellectual ability for healthy adults (Docherty et al, 2015; Gregory et al, 2016) and individuals with neurodevelopmental disorders (Lukoshe et al, 2014; Treble et al, 2013). Even though these interaction effects were found for all tests examined and in widespread frontoparietal cortices, statistical mediation analyses showed age-related changes in cortical folding causally influenced only motor response inhibition ability.…”
Section: Discussionmentioning
confidence: 86%
“…Non-food-stimulated resting-state studies have also implicated a deregulation of energy intake and impairment in inhibitory control in PWS [Zhang et al, 2013[Zhang et al, , 2015. Only a few studies have focused on anatomical alterations in PWS [Lukoshe et al, 2014;Ogura et al, 2011;Yamada et al, 2006]. Compared with controls, PWS subjects exhibited smaller gray matter volumes [Ogura et al, 2011], reduced cortical complexity [Lukoshe et al, 2014], and decreased white matter integrity [Yamada et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…MRI studies in PWS suggested that lower cortical complexity partially underlies cognitive impairment and developmental delay [4], with structural brain abnormalities and different neurodevelopmental patterns between children with a deletion and an mUPD [5]. Certain cognitive skills improved significantly during GH treatment, while GH-untreated children with PWS showed a deterioration of cognitive functioning [6, 7].…”
Section: Introductionmentioning
confidence: 99%